The Satisfied Patient 2.0: Analysis of anonymous doctor ratings to gain insight into patient sentimen - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)

Selektive Vertriebssysteme am Fallbeispiel der Adidas AG - eine wettbewerbspolitische Beurteilung - Zindler, Finn

Playing the Lottery or Dressing Up? A Model of Firm-Level Heterogeneity and the Decision to Export - Gries, Thomas; Naudé, Wim; Bilkic, Natascha (The Quarterly Review of Economics and Finance)

Changes of China’s agri-food exports to Germany caused by its accession to WTO and the 2008 financial crisis - Gries, Thomas; Feng, Yuanhua; Guo, Zhichao (China Agricultural Economic Review)

Koordinierter Patentschutz in einer globalisierten Welt - Effizienz- und Anreizwirkungen auf die Arzneimittelversorgung in Entwicklungsländern - Kirsch, Michelle

Economics and Value of IS - Han, K.; Kundisch, Dennis; Weinhardt, C.; Zimmermann, Steffen

Rating Aggregation in Multi-Dimensional Rating Systems: How Do Reviewers Form Overall Ratings? - Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

Unscharfe Produktionsmengenplanung als Instrument des Risikomanagements in Supply Chains - Betz, Stefan (Risikomanagement in Supply Chains)

Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Optimierung von Wasserbehältern in einem Wasserversorgungssystem mittels einer Kombination aus Netzreduktion, mathematischer Optimierung und hydraulischer Simulation - Hallmann, Corinna

Will They Die Another Day? A Decision Support Perspective on Reusing Electric Vehicle Batteries - Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

A Market for Trading Used Electric Vehicle Batteries — Theoretical Foundations and Information Systems - Klör, Benjamin; Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

Sustaining Civil Peace: a configurational comparative analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Oppressive Governments, Dependence on the United States and Anti-American Terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)

Erfolg durch Persönlichkeit? Der Einfluss der Markenpersönlichkeit auf den Zusammenhang von Reputation und Unternehmenserfolg - Fanasch, Patrizia

Die Veränderung des Mobilfunkmarktes durch die Discountanbieter - Walczok, Gregor Paul

A Domain-Specific Modeling Language for Electric Vehicle Batteries - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Monhof, Markus (Proceedings of the 12. International Conference on Wirtschaftsinformatik 2015 (WI 2015))

Extending Battery Management Systems for Making Informed Decisions on Battery Reuse - Monhof, Markus; Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian (New Horizons in Design Science: Broadening the Research Agenda)

Neue Bildungslandschaften - Kommunales Bildungsmanagement als Zukunftsaufgabe - Euler, Dieter; Sloane, Peter F. E. (Zeitschrift für Berufs-und Wirtschaftspädagogik)

How do reviews from professional critics interact with other signals of product quality? Evidence from the video game industry - Cox, Joe; Kaimann, Daniel (Journal of Consumer Behaviour)
Experience goods are characterised by information asymmetry and a lack of ex ante knowledge of product quality, such that reliable external signals of quality are likely to be highly valued. Two potentially credible sources of such information are reviews from professional critics and ‘word of mouth’ from other consumers. This paper makes a direct comparison between the relative influences and interactions of reviews from both of these sources on the sales performance of video game software. In order to empirically estimate and separate the effects of the two signals, we analyze a sample of 1480 video games and their sales figures between 2004 and 2010. We find evidence to suggest that even after taking steps to control for endogeneity, reviews from professional critics have a significantly positive influence on sales which outweighs that from consumer reviews. We also find evidence to suggest that reviews from professional critics also interact significantly with other signals of product quality. Consequently, we contend that professional critics adopt the role of an influencer, whereas word-of-mouth opinion acts more as a predictor of sales in the market for video games.

How do Different Sources of the Variance of Consumer Ratings Matter? - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth)
We examine the effect of the variance of consumer ratings on product pricing and sales using an analytical model, which considers goods that are characterized by experience attributes and informed search attributes (i.e., experience attributes that were transformed in search attributes by consumer ratings). For pure informed search goods, equilibrium price increases and demand decreases in variance. For pure experience goods, equilibrium price and demand decrease in variance. For hybrid goods with low total variance, equilibrium price and demand increase with an increasing relative share of variance caused by informed search attributes when the average rating and total variance of ratings are held constant. Hence, risk-averse consumers may prefer a more expensive good with a higher variance of ratings out of two similar goods with the same average rating. Moreover, our analytical model provides a theoretical foundation for the empirically observed j-shaped distribution of consumer ratings in electronic commerce.

Fusionen von gesetzlichen Krankenversicherungen zu den Effizienz- und Wechselwirkungen - Osburg, Christina

Fair Trade - Eine neue Perspektive in der internationalen Handelspolitik - Materna, GinaJoanna

Fair Trade - An economic investigation of benefits and drawbacks - Goronczewski, Patricia

Entwicklung von Ablösesummen und Gehälter in der Fußball-Bundesliga - Salary Caps als mögliches Modell der Chancengleichheit - Plonka, Dennis

Ausgewählte Probleme des Logistikmanagements

Diffusion of Innovations in Social Networks - Kunisch, Christina

Die Einführung der EU-Merger Guidelines - Effizienz und Wohlfahrtswirkungen - Topal, Barlas

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

DUC - Fostering Diversity Aspects in Higher Education by eLearning and User generated Content - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Rechuel, R. (Proceedings of E-LEARN 2015 - World Conference on E-Learning)

Behavioral Mechanisms Prompted by Virtual Rewards: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the 23rd European Conference on Information Systems (ECIS))

Interactions in IS Project Portfolio Selection: Status Quo and Perspective - Müller, M.; Meier, Christian; Kundisch, Dennis; Zimmermann, Steffen (Wirtschaftsinformatik Proceedings)

Creativity Through Cognitive Fit: Theory and Preliminary Evidence in a Business Model Idea Generation Context - John, Thomas; Kundisch, Dennis (Wirtschaftsinformatik Proceedings)

Does technological change drive inclusive industrialization? - A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

Disentangling the Role of Contract Types and Sector Disparities for Public Service Motivation - Grund, Christian; Thommes, Kirsten
The intention of "doing good for society" is regarded to be a crucial motivator for employees in the public sector in order for them to perform well. Recent research in the public sector literature calls for a deeper understanding of how this specific public service motivation (PSM) is shaped. In our paper, we analyze how different degrees of inclusion in the public sector impact PSM. We also investigate how prospects of employment relations (fixed-term versus permanent contracts), temporal differences (part-time versus full-time employment), and actual jobs (core versus subsidiary jobs) moderate PSM in public service. Our findings show that aspects of PSM are affected by these employment characteristics in various ways, suggesting that the factors influencing PSM are multifaceted and that actual employment conditions have to be taken into consideration when assessing PSM.

Cooperation in Diverse Teams: The Role of Temporary Group Membership - Grund, Christian; Harbring, Christine; Thommes, Kirsten
In organizations, some team members are assigned to a team for a predefined short period of time, e.g., as they have a temporary contract, while others are permanent members of the same team. In a laboratory experiment we analyze the cooperation levels resulting from diverse teams, where some team members remain with a team and others are switching teams. Our results reveal that teams consisting partly of members with temporary membership display a lower productivity compared to teams of permanent team members only. First, temporary team members cooperate less than permanent team members. Second, individual effort decisions increase with the number of team mates who are of the same type. This second effect holds for both temps and permanents. We argue that social identity is affected by team composition and the individuals' role in a team.

Verkaufsbeschränkungen auf Onlinemarktplätzen - Eine wettbewerbspolitische Analyse am Fallbeispiel der Adidas AG - Menne, Maria Reinhild

The Effect of Taxes on Corporate Financing Decisions - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren
The literature suggests that when taking tax effects into account, debt ought to be prefer-able to equity. Thus, with all else being equal, levered firms are expected to show higher firm values.However, there are no uniform predictions of the size of this tax benefit from interest deductibility nor on the effect of changes in interest deductibility. We believe that the German corporate tax re-form in 2008, which introduced an interest barrier, can serve as a promising “quasi-experiment” to investigate the effects from a reform of interest deductibility. A study of this reform on the basis of German financial statement data is of general interest because, first, similar interest barriers have been introduced in several countries and proposed by the OECD to fight BEPS. Second, the major characteristics of the German tax system can be regarded as representative for most European and major Asian countries. Third, single entity financial statements for German companies allows us to capture tax and capital structure details that have not been available in most prior studies. With significance at the 5% level, we find evidence that the companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than companies that are not affected by the interest barrier. We are the first to employ a detailed matching approach to the underlying rich dataset, which enables us to overcome several limitations of previous studies. Our results imply that capital structure reactions most likely have been underestimated in previous studies.

“…and they are really lying”: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment. - Fahr, Rene; Mir Djawadi, Behnud (Journal of Economic Psychology)
We investigate the pervasiveness of lying in professional contexts such as insurance fraud, tax evasion and untrue job applications. We argue that lying in professional contexts share three characterizing features: (1) the gain from the dishonest behavior is uncertain, (2) the harm that lying may cause to the other party is only indirect and (3) lies are more indirect lies by action or written statements. Conducted as a field experiment with a heterogenous group of participants during a University ‘‘Open House Day’’, our ‘‘gumball-machineexperiment’’ provides field evidence on how preferences for lying are shaped in situations typically found in professional contexts which we consider to be particularly prone to lying behavior compared to other contexts. As a key innovation, our experimental design allows measuring exact levels of cheating behavior under anonymous conditions. We find clean evidence that cheating is prevalent across all sub groups and that more than 32% of the population cheats for their own gain. However, an analysis of the cheating rates with respect to highest educational degree and professional status reveals that students cheat more than non-students. This finding warrants a careful interpretation of generalizing laboratory findings with student subjects about the prevalence of cheating in the population.

Zur Verbreitung von Informationen in sozialen Netzwerken - eine wirtschaftspolitische Analyse - Schulz, Hannah

Why Fit Leads to Surprise: An Extension of Cognitive Fit Theory to Creative Problems - John, Thomas; Kundisch, Dennis (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth, USA)
Cognitive fit theory (CFT) provides guidance for how best to represent information that is relevant for solving a given problem. CFT is widely established in information systems research and its validity has been demonstrated in a great variety of contexts. However, of the two major types of problems that exist (i.e., routine and creative problems) prior CFT research has addressed only one: routine problems. Creative problems, despite their importance, have been left unaddressed. Therefore, based on the visual sketching model of problem solving, we propose an extension of CFT and thereby demonstrate that cognitive fit can promote problem solving performance also for creative problems. In doing so, we extend the boundary of CFT and add to creativity research a previously unknown cognitive mechanism for promoting creative performance: cognitive fit. Moreover, we contribute to general problem solving research by bridging the gap between problem solving in creativity and information systems research.

You Might Want to Engage Your Customers, But Choose Them Wisely: The Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty - Eggert, A; Steinhoff, L; Witte, C (2015 AMA Summer Marketing Educators' Conference Proceedings)

Stock Market Reactions to Business Service Outsourcing in Manufacturing Firms - Cramer, C; Böhm, E; Eggert, A (Proceedings of the 44th European Marketing Academy (EMAC) Conference)

Threatening customers not to return – An effective strategy for online retailers? - Feider, L; Garnefeld, I; Böhm, E (Proceedings of the 44th European Marketing Academy (EMAC) Conference)

High-Performance Computing for Scheduling Decision Support: A Parallel Depth-First Search Heuristic - Rauchecker, Gerhard; Schryen, Guido (Australasian Conference on Information Systems)
Many academic disciplines - including information systems, computer science, and operations management - face scheduling problems as important decision making tasks. Since many scheduling problems are NP-hard in the strong sense, there is a need for developing solution heuristics. For scheduling problems with setup times on unrelated parallel machines, there is limited research on solution methods and to the best of our knowledge, parallel computer architectures have not yet been taken advantage of. We address this gap by proposing and implementing a new solution heuristic and by testing different parallelization strategies. In our computational experiments, we show that our heuristic calculates near-optimal solutions even for large instances and that computing time can be reduced substantially by our parallelization approach.
Keywords: scheduling; decision support; heuristic; high performance computing; parallel algorithms

Revenue Management for Cloud Computing Providers: Decision Models for Service Admission Control under Non-probabilistic Uncertainty - Püschel, Tim; Schryen, Guido; Hristova, Diana; Neumann, Dirk (European Journal of Operational Research)
Cloud computing promises the flexible delivery of computing services in a pay-as-you-go manner. It allows customers to easily scale their infrastructure and save on the overall cost of operation. However Cloud service offerings can only thrive if customers are satisfied with service performance. Allow-ing instantaneous access and flexible scaling while maintaining the service levels and offering competitive prices poses a significant challenge to Cloud Computing providers. Furthermore services will remain available in the long run only if this business generates a stable revenue stream. To address these challenges we introduce novel policy-based service admission control mod-els that aim at maximizing the revenue of Cloud providers while taking in-formational uncertainty regarding resource requirements into account. Our evaluation shows that policy-based approaches statistically significantly out-perform first come first serve approaches, which are still state of the art. Furthermore the results give insights in how and to what extent uncertainty has a negative impact on revenue.
Keywords: admission control; informational uncertainty; revenue management; cloud computing

Futurizing” Smart Service: Implications for Service Researchers and Managers. - Wünderlich, Nancy; Heinonen, Kristina; Ostrom, Amy L; Patricio, Lia; Sousa, Rui; Voss, Chris; Lemmink, Jos (Journal of Services Marketing)
Purpose – The purpose of this paper is to craft a future research agenda to advance smart service research and practice. Smart services are delivered to or via intelligent objects that feature awareness and connectivity. For service researchers and managers, one of the most fascinating aspects of smart service provision is that the connected object is able to sense its own condition and its surroundings and thus allows for real-time data collection, continuous communication and interactive feedback. Design/methodology/approach – This article is based on discussions in the workshop on “Fresh perspectives on technology in service” at the International Network of Service Researchers on September 26, 2014 at CTF, Karlstad, Sweden. The paper summarizes the discussion on smart services, adds an extensive literature review, provides examples from business practice and develops a structured approach to new research avenues. Findings – We propose that smart services vary on their individual level of autonomous decision-making, visibility and embeddedness in objects and customer lives. Based on a discussion of these characteristics, we identify research avenues regarding the perception and nature of smart services, the adoption of smart services, the innovation through smart services as well as regarding the development of new business models. Originality/value – Smart services is a new emerging topic in service marketing research, their implications on organizations, customers and the service landscape have not been fully explored. We provide a fresh perspective on service research by characterizing relevant aspects of smart service that will stimulate fruitful future research and advance the understanding and practice of smart services.
Keywords: Connected services; Intelligent object; New service type; Smart services

Conducting Service Research that Matters. - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K; McColl-Kennedy, Janet R; Sirianni, Nancy J; Witell, Lars; Wünderlich, Nancy (Journal of Services Marketing)
Purpose – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.
Keywords: Relevance; Service technology; Service innovation; Customer experience; Rigor; Service outcomes

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

Bilateral matching and bargaining games - Mikroökonomie, Lehrstuhl

Komplexe Selbstlernaufgabe (,WiWi-Studies') in der Eingangsphase wirtschaftswissenschaftlicher Bachelorstudiengänge. Einblicke in ein Design-Based Research-Projekt mit Studierendenbefragungen - Zoyke, A.; Kremer, H.-Hugo; Sampaio-Araujo, J. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

What does Vocational Mean? Exploring the Understanding of Vocational in Higher Education and Vocational Education - Kremer, H.-Hugo; Rüschen, E. (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings)

Gestaltung der Studieneingangsphase an einer wirtschaftswissenschaftlichen Fakultät - Kerbs, N.; Kremer, H.-Hugo; Rüschen, E.; Sampaio-Araujo, J.; Zoyke, A. (Das Hochschulwesen)

Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung: Das Forschungs- und Entwicklungsprojekt InBig - Beutner, Marc; Kremer, H.-Hugo; Kundisch, Heike; Rohde, S.; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Überlegungen zur Modellierung der Bildungsarbeit im Rahmen von InBig - Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Enwticklungsprojekt InBig)

Bildungsgangarbeit an Berufskollegs. Diskussionsbericht zur Bestandserhebung an den Pilot-Berufskollegs im Projekt InBig - Kranert, T.; Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Grundstrukturen und Arbeitsbasis - Zur Entwicklung der Standortkonzepte - InBig als Forschungsfrage und Entwicklungsarena - Kremer, H.-Hugo; Beutner, Marc; Kranert, T. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Robert-Bosch-Berufskolleg der Stadt Dortmund - Rose, S.; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Berufskollegs Ernährung, Sozialwesen, Technik in Geilenkirchen - Beutner, Marc; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

,Voraussetzungen und Möglichkeiten der Gestaltung gemeinsamen Lernens für Jugendliche mit sonderpädagogischem Förderbedarf im Bereich Lern- und Entwicklungsstörungen' im Auftrag des Ministeriums für Schule und Weiterbildung des Landes Nordrhein-Westfalen - Kremer, H.-Hugo; Kückmann, Marie-Ann; Sloane, Peter F. E.; Zoyke, A.

Praxisformate in der Ausbildungsvorbereitung - Beutner, Marc; Eickhoff, A.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kollegiale Weiterbildung. Entwicklung, Qualifizierung und Rollenverschärfung für Nachwuchsführungskräfte an Berufskollegs - Kundisch, Heike; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Multiprofessionelle Teamarbeit - Notwendigkeit und (schleichende) Veränderung von Berufskollegs - Kückmann, Marie-Ann; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Auf dem Wege zur Qualität in der Ausbildungsvorbereitung - Einblicke in Prozesse zur Entwicklung und Implementation innovativer Konzepte - Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionn aus dem Forschungs- und Entwicklungsprojekt InBig)

Entwicklung von Berufskollegs - Handlungsfelder, Herausforderungen und Unterstützungsbedarf von Nachwuchsführungskräften in der Beruflichen Bildung - Kremer, H.-Hugo; Kundisch, Heike; Schreiner, K. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsarbeit. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Erleben Schulischer Wirklichkeit - Schulische Langeweile aus Sicht von Jugendlichen an Berufskollegs - Dirksmeier, V.; Gonsior, R.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kein Ende...vor dem Anfang einer weiteren Professionalisierung der Bildungsarbeit - Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari

Pädagogische Hochschulentwicklung: Von der Programmatik zur Implementierung - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
Der Sammelband befasst sich mit einem umfassenden Ansatz zur Verbesserung der Qualität von Lehre und Studium. Mit dem Konzept der pädagogischen Hochschulentwicklung plädieren die AutorInnen dafür, bei der Umsetzung von Veränderungsprojekten die verschiedenen Ebenen der Hochschule zu verschränken. Zum Beispiel sollten Initiativen, die eine Lehrveranstaltung betreffen, idealerweise die (Aus )Wirkungen auf den Ebenen der Studienprogramme und der Organisation berücksichtigen und aktiv gestalten. Die einzelnen Beiträge stellen beispielhafte Initiativen aus unterschiedlichen Disziplinen und Hochschulformen dar und illustrieren, wie die genannten Ebenen in der praktischen Umsetzung verzahnt werden können.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

How Do They Find Their Place? A Longitudinal Study of Management Students' Attitudes and Motivations During Their First Year at Business School - Jenert, Tobias; Brahm, Taiga
The first year of studying has been extensively researched applying different theoretical lenses to better understand the transition into Higher Education (HE). It is of particular interest to investigate how students deal with frictions between themselves as individuals and what they perceive to be dominant features of the first-year culture of their studies. To tackle this question, a qualitative longitudinal study was conducted. Based on a sociocultural understanding of attitudes and motivations, its aim was to closely follow a relatively small but highly diverse sample of students throughout their first year at a business school in order to develop an in-depth understanding of each individual’s motivational and attitudinal development.
Keywords: Enculturation; first-year students; beginning students; retention; drop-out

The crucial first year: Students’ motivation at a Swiss Business School--a longitudinal study - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Academy of Management Proceedings)
Despite students’ motivation being considered a strong predictor of performance, the development of motivation of business school students has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. This is surprising, as the transition from school to university is a crucial phase in the academic career and can be overwhelming for some students. The present study addresses this research gap and examines the development of economics and management students’ study motivation. The longitudinal study included four waves of data collected throughout the first year using quantitative surveys. Regarding students’ development over time, the analysis showed a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline

Zwischen Individuum, Institution und Disziplin: Methodologische Überlegungen zur Erfassung von Lernkulturen an Hochschule - Jenert, Tobias; Reinmann, Gabi (Dokumentation der Jahrestagung der Sektion Erwachsenenbildung der DGfE)
Keywords: Methodologie; Lernforschung; hochschuldidaktische Forschung; Higher Education

Zwischen" netten" Tools und" Überdidaktisierung": Neue Medien in der Hochschuldidaktik - Wagner, Dietrich; Jenert, Tobias
Auswertung einer Befragung unter Studierenden zu der Frage welche Elemente eine Lehrveranstaltung innovativ machen und welche Rolle die neuen Medien dabei spielen. Digitale Medien begegnen uns in der Hochschule immer wieder. Häufig handelt es sich um neue Werkzeuge oder Trends (Klicker, MOOCs, Web 2.0), die einerseits potenzialreich und spannend erscheinen, deren didaktische Verwertbarkeit sich aber nicht auf den ersten Blick erschließt. Oft folgt nach einer euphorischen Erprobung schnell die Ernüchterung, wenn festgestellt wird, dass sich durch die digitalen Technologien allein kein erhöhter Lernerfolg ergibt und auch die Studierenden keine nachhaltigen Motivationsschübe erfahren. Aus der Hochschuldidaktik hört man häufig und berechtigterweise kritische Stimmen, welche die Einbettung digitaler Medien in sorgfältig geplante didaktische Arrangements betonen. Es stellt sich die Frage, inwieweit damit die Kreativität und der Entdeckergeist von Lehrenden und Studierenden eingeschränkt werden. Wir wollen im Disq-Space der Frage nachgehen, wie die Hochschuldidaktik auf neue digitale Trends reagieren und dabei einen Mittelweg zwischen "kreativem Ausprobieren" und pädagogisch-didaktischer Rationalität einschlagen kann. Zunächst werden die Ergebnisse einer aktuellen Umfrage an der Universität St. Gallen zu den Vorstellungen Studierender zu innovativer Lehre vorgestellt. Nach einer Öffnung des Raums für gute sowie schlechte Erfahrungen und Bespiele von Seiten der Teilnehmenden soll diskutiert werden, welche personellen, didaktischen und organisatorischen Voraussetzungen erfüllt sein müssen, damit Digitalisierung die Kompetenzentwicklung der Studierenden unterstützt. Die Ergebnisse der Diskussionsrunde werden im Blog des Teams Hochschulentwicklung zur Verfügung gestellt. Es wird angestrebt, diese damit einer breiteren Öffentlichkeit zugänglich zu machen.
Keywords: Neue Medien; Hochschuldidaktik; Studierende; Innovation in der Lehre

On the iterative plug-in algorithm for estimating diurnal patterns of financial trade durations - Feng, Yuanhua; Forstinger, Sarah; Peitz, Christian (Journal of Statistical Computation and Simulation)

Forecasting financial market activity using a semiparametric fractionally integrated Log-ACD - Feng, Yuanhua; Zhou, Chen (International Journal of Forecasting)

Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Formula Apportionment or Separate Accounting? Tax-Induced Distortions of Multinationals' Locational Investment Decisions - Ortmann, Regina; Pummerer, Erich

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren

The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho, Harri; Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang (Industrial Marketing Management)

Heading for new shores: Do service and hybrid innovations outperform product innovations in industrial companies? - Eggert, Andreas; Thiesbrummel, Christoph; Deutscher, Christian (Industrial Marketing Management)

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 3 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Wertbasiertes Verkaufen auf Industriegütermärkten - Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang; Terho, Harri (Handbuch Business-to-Business-Marketing)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences